Guided Imagery and Anger Management Interventions for Reducing Aggressive Behavior in Older Adults at the Pangudi Luhur Integrated Care Center, Bekasi: TEKNIK IMAJINASI TERBIMBING DENGAN MANAJEMEN KEMARAHAN TERHADAP PENURUNAN PERILAKU AGRESIF LANJUT USIA DI SENTRA TERPADU PANGUDI LUHUR BEKASI - Zainab, Zennyca; Susilawati, Susilawati; Kartika, Tuti (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2025)
Aggressive behavior is a significant issue experienced by the elderly, with various factors and backgrounds. Guided imagery is one of the intervention techniques used to address aggressive behavior at the Sentra Terpadu Pangudi Luhur (STPL) in Bekasi. However, this technique is not yet optimal and has weaknesses in addressing aggressive behavior. Addressing aggressive behavior is a crucial issue for improving the psychosocial well-being of the elderly. The design of a guided imagery technique with anger management has been designed to address this issue and address the weaknesses of previous technologies. This study aims to test the guided imagery technique with anger management by integrating steps from both techniques, aiming to reduce aggressive behavior in the elderly. The research method used a Single Subject Design (SSD) with three subjects using an A-B-A reversal design. Data collection tools used observation with behavioral targets, namely physical attacks, swearing, and threats. Supplemented with the Buss–Perry Aggression Questionnaire (BPAQ), interviews, and documentation studies. Validity tests used interface validity, while reliability tests used percent agreement. Data analysis used analysis within and between conditions. The research results showed that the application of this technique was proven effective in reducing aggressive behavior, as evidenced by the decrease in the baseline A2 phase. These results were supported by the testimony of social workers who observed aggressive behavior before and after the intervention. However, this technique requires experimental methods involving more subjects to ensure its generalizability and should be repeated as needed